2016
DOI: 10.3390/f7100222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topographical and Edaphic Factors on Tree Community Structure and Diversity of Subtropical Mountain Forests in the Lower Lancang River Basin

Abstract: Abstract:We investigated community structure and tree species diversity of six subtropical mountain forests in relation to 11 topographical and edaphic factors in Lower Lancang River Basin, Yunnan Province, China, based on a census of all trees with diameter at breast height ≥5 cm in 45 0.06-ha plots. The forests were as follows: a river valley monsoon forest, semi-humid evergreen broad-leaved forest, monsoon evergreen broad-leaved forest, mid-mountain humid evergreen broad-leaved forest, summit mossy dwarf fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…For instance, Cui and Zheng (2016) and Homeier et al (2010) observed significantly higher tree species diversity at lower slope position in comparison with upper slope sites. However, a study by Zhang et al (2016) in mountain forest in China showed such relationships nonsignificant. These outcomes suggest that the effects of slope on taxonomic diversity may partly depend on other factors such as the scale of the study and the magnitude of the slope gradient.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, Cui and Zheng (2016) and Homeier et al (2010) observed significantly higher tree species diversity at lower slope position in comparison with upper slope sites. However, a study by Zhang et al (2016) in mountain forest in China showed such relationships nonsignificant. These outcomes suggest that the effects of slope on taxonomic diversity may partly depend on other factors such as the scale of the study and the magnitude of the slope gradient.…”
Section: Discussionmentioning
confidence: 92%
“…At larger scales, climatic conditions may influence an organism's life cycle and performance, whereas, at smaller scales, local environmental variation in edaphic or topographic factors (elevation, aspect, slope, etc. ), resources availability, and species competitive abilities would likely codetermine species structural and dominance patterns (Mensah, Salako, Assogbadjo, & Gle`le`Kakaı¨, 2018;Zhang, Chen, Liu, & Pei, 2016). For example, environmental factors such as soil physical properties and slope were pointed out as potential drivers of vegetation structure and distribution (Gonc¸alves, Filho, Vendrame, & Telles, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the edaphic and topographic influence on forest development is essential for rational management of forest and soil. Studies relating forest development to soil conditions are common for native forests (Zhang et al, 2016;Mendonça et al, 2017;Oberhuber, 2017;Soboleski et al, 2017 ), showing the strict relationship between soil, relief, and forest, and highlighting the importance of studying these relationships at the landscape scale. However, in commercial forests, these relations are not clear, especially in rugged terrain where relationships between the landscape, soil, and plants are more complex.…”
Section: Introductionmentioning
confidence: 99%